A Phase II Randomized Clinical Trial and Mechanistic Studies Using Improved Probiotics to Prevent Oral Mucositis Induced by Concurrent Radiotherapy and Chemotherapy in Nasopharyngeal Carcinoma - Xia, Chaofei; Jiang, Chunling; Li, Wenyu; Wei, Jing; Hong, Hu; Li, Jingao; Feng, Liu; Wei, Hong; Xin, Hongbo; Chen, Tingtao (Frontiers in Immunology, 2021)
Earlier evidence has proven that probiotic supplements can reduce concurrent chemoradiotherapy (CCRT)-induced oral mucositis (OM) in nasopharyngeal cancer (NPC). The incidence of severe OM (grade 3 or higher) was the primary endpoint in this study. We first enrolled 85 patients with locally advanced NPC who were undergoing CCRT. Of them, 77 patients were finally selected and randomized (1:1) to receive either a probiotic cocktail or placebo. To investigate the protective effects and the mechanism of probiotic cocktail treatment on OM induced by radiotherapy and chemotherapy, we randomly divided the rats into the control (C) group, the model (M) group, and the probiotic (P) group. After treatment, samples from the tongue, blood, and fecal and proximal colon tissues on various days (7th, 14th, and 21st days) were collected and tested for the inflammatory response, cell apoptosis, intestinal permeability, and intestinal microbial changes. We found that patients taking the probiotic cocktail showed significantly lower OM. The values of the incidence of 0, 1, 2, 3, and 4 grades of OM in the placebo group and in the probiotic cocktail group were reported to be 0, 14.7, 38.2, 32.4, and 14.7% and 13.9, 36.1, 25, 22.2, and 2.8%, respectively. Furthermore, patients in the probiotic cocktail group showed a decrease in the reduction rate of CD3+ T cells (75.5% vs. 81%, p < 0.01), CD4+ T cells (64.53% vs. 79.53%, p < 0.01), and CD8+ T cells (75.59 vs. 62.36%, p < 0.01) compared to the placebo group. In the rat model, the probiotic cocktail could ameliorate the severity of OM, decrease the inflammatory response, cause cell apoptosis and intestinal permeability, and restore the structure of gut microbiota to normalcy. In conclusion, the modified probiotic cocktail significantly reduces the severity of OM by enhancing the immune response of patients with NPC and modifying the structure of gut microbiota. Clinical Trial Registration: The Clinical Trial Registration should be the NCT03112837.